Effect of tricalcium phosphate on healing of non-unions: an observational study of over 400 non-unions - Ferbert, Thomas; Münch, Christina; Findeisen, Sebastian; Pauly, William; Miska, Matthias; Großner, Tobias; Tanner, Michael Christopher; Schmidmaier, Gerhard; Helbig, Lars (Therapeutics and clinical risk management, 2023)
Effect of Tricalcium Phosphate on Healing of Non-Unions: An Observational Study of over 400 Non-Unions